DEVELOPMENT STRATEGY OF EAST JAVA TOURISM AS AN ALTERNATIVE SOURCE OF ECONOMIC GROWTH - Abraham Risyad Al Faruqi; Faizal Rahmanto Moeis; Kurniawati Yuli Ashar (East Java Economic Journal, 2018)
The economic condition of East Java has been good lately by consistently having economic growth above the national economic growth and consistently contributing above 14% of Indonesia’s GDP from 2011 to 2016. However, lately East Java’s economy has slowed down due to the slowing down of its main industry sector, which is the manucfacturing sector. Looking by the growth trend that continues to increase, the tourism sector is considered to be a promising sector as an alternative source of economic growth in East Java. Other than that, to consider tourism sector as an alternative source of growth, we must see the linkage of the tourism sector to other industry sectors. This will be proven by using the Input-Output Analysis and the tourism sector is proven to have a wide linkage to other industry sectors. The strategy analysis of the development of tourism sector as a growth alternative source is continued by using the panel data regression with model developed by Joshi, Pouydal, & Larson (2017) with the study case of 30 provinces in Indonesia from the year 2010-2015. This analysis will also be linked to the model of tourism multiplier. Based on the analysis, there are 3 strategies for the development of tourism sector, which is increasing the conducive socioeconomic conditions, development of tourism infrastructure, and development of tourism resources.